Produktivitas Jagung (Zea mays L.) pada Berbagai Tingkat Naungan Tanaman Kelapa (Cocos nucifera L.) - JOHANNES E.X. ROGI; J. I. KALANGI; JOHAN A. ROMBANG; A. LUMINGKEWAS; S. TUMBELAKA; YULIA PASKALINA (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
Productivity of Corn (Zea mays L.) at Various Levels of Shading inCoconut Field (Cocos nucifera L.)Coconut cultivation in monoculture had problems in field production, processing and marketing that can cause low coconut farmers income. Therefore we need coconut farm diversification by increasing the potential of land among the coconut trees. Area of land that used coconut palm is only about 20% so that the remaining land that can be used for other commodities is 80%. One of the plants can be cultivated among the coconut is corn. Land use among the coconut palm is expected to increase corn production because corn is one of the leading food commodities and the potential in Indonesia. The objective of this study to determine the productivity of corn plants at different levels of shade by coconut palm. The research was conducted at the experimental Garden Kima Atas, Indonesia Coconut and Other Palm Research Institute (ICOPRI), North Sulawesi. This research was conducted from June to November 2007. The results showed that an increase in production of plant dry weight in treatment D (corn planted in open areas) is higher than treatment A (corn grown in between coconut palm old), B (corn grown inbetween coconut palm 20 years old) and C (corn grown in between coconut palm 50 years old).